Norms on laity (Code of Canon Law 1917 can. 682-725). In search of an ecclesiastical interpretation - BACH-GOLECKA, DOBROCHNA (Prawo Kanoniczne, 2019)
The main subject of the article is focused upon the analysis of the provisions of the Code of Canon Law of 1917 on laity. Those provisions are contained in the third part of the second book on persons and are enlisted in solely 43 canons. The fundamental provision among those seems to be can. 682 stipulating the rights of laity of receiving from the clergy, according to the norm of ecclesiastical discipline, spiritual goods and especially that aid necessary for salvation. Other provisions concerning laity are focused upon procedural aspects of associations of the faithful, like third orders, archconfraternities and confraternities, pious unions (can. 684-725). Moreover, other rights and obligations of the laity provided for in the Code are identified in order to establish the functional ecclesiastic relationship between the clergy and laity. The modest regulation on laity within the Code of Canon Law of 1917 is contrasted to the vast number of provisions of the Code of Canon Law of 1983, whereas the second book of the Code is dealing with the Christ’s faithful. It seems that the abundance of provisions on laity may be explained by the influence of the Second Vatican Council. Within this comparative perspective the laity provisions of the Code of Canon Law of 1917 may be regarded as an evolutionary regulation, necessary in order to establish solid foundations of the Church’s functioning within the modern era. Therefore the codification of canon law of 1917 should be evaluated as an result of the regulatory effort of the Church emerging from the circumstances of the First World War perspective and the dawn of the contemporary period.